2020
DOI: 10.1163/15718182-02801003
|View full text |Cite
|
Sign up to set email alerts
|

Educational Children’s Rights Research 1989–2019: Achievements, Gaps and Future Prospects

Abstract: Since the adoption of the United Nations Convention on the Rights of the Child in 1989, research into children’s rights issues in educational contexts has grown significantly. This paper takes stock of the evolution of educational children’s rights research, and provides a characterisation of the research field. By means of a systematic analysis of the published scholarship, the main achievements of the research are identified, as well as gaps in knowledge production. Major research foci are highlighted, the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 86 publications
0
5
0
1
Order By: Relevance
“…In schools, such flexibility is often complex. Thus, it is not surprising that some studies have indicated that the opportunities for pupils to be heard and have their views respected are rather limited (for a review, see Quennerstedt & Moody, 2020).…”
Section: Children's Right To Participate In Decision-makingmentioning
confidence: 99%
“…In schools, such flexibility is often complex. Thus, it is not surprising that some studies have indicated that the opportunities for pupils to be heard and have their views respected are rather limited (for a review, see Quennerstedt & Moody, 2020).…”
Section: Children's Right To Participate In Decision-makingmentioning
confidence: 99%
“…At this stage, a further search was conducted based on complementary search methods-follow-up of references, citation searching, and citation pearl growing (i.e., using one relevant source to identify additional relevant sources)-to identify relevant empirical studies meeting the search criteria that had not been captured by the electronic search (see Cooke et al, 2012). I also reviewed the references of articles that conducted systematic reviews on related issues (Mager & Nowak, 2012;Quennerstedt, 2011;Quennerstedt & Moody, 2020;Urinboyev et al, 2016).…”
Section: 13mentioning
confidence: 99%
“…It aims to characterize students' perceptions of their rights in school and explore the factors influencing these perceptions. Since the ratification of the United Nations Convention on the Rights of the Child (UNCRC) in 1989, scholarly interest in students' rights has grown (see Byrne & Lundy, 2019;Todres & King, 2020;Quennerstedt & Moody, 2020;United Nations, 1989). In the United States, which has yet to ratify the UNCRC, this interest is linked to principles of equal protection and racial justice (Morrill et al, 2010;Preiss et al, 2016) and the pivotal role of children's rights in American constitutional law (Todres et al, 2006;Woodhouse, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Une revue systématique est moins stricte qu'une méta-analyse quant au respect de certaines procédures ; dans un tel cas, il n'y a, par exemple, pas d'évaluation spécifique de qualité outre celui de l'examen par les pair•e•s pour publication, lequel est jugé adéquat pour l'analyse d'un échantillon représentatif de la littérature existante. Une troisième conceptualisation est la synthèse de recherches, laquelle n'a pas pour ambition d'établir des preuves ou de synthétiser des résultats, mais d'identifier des caractéristiques, des modèles voire les modes d'organisation des connaissances au sujet d'un objet donné et ainsi créer des connaissances qui vont au-delà de la simple addition des connaissances existantes à ce sujet (Andrews et Harlen, 2006 ;Quennerstedt, 2011 ;Quennerstedt et Moody, 2020 ;Soilemezi et Linceviciute, 2018 ;Sutcliffe et al, 2012).…”
Section: Méthodologie Et Objectifsunclassified